2017
DOI: 10.1016/j.bios.2016.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between avidin and graphene for development of a biosensing platform

Abstract: Fundamental understanding of interactions at the interface of biological molecules, such as proteins, and nanomaterials is crucial for developing various biocompatible hybrid materials and biosensing platforms. Biosensors comprising of graphene-based conductive nanomaterials offer the advantage of higher sensitivity and reliable diagnosis mainly due to their superior specific surface area and ballistic conductivity. Furthermore, conductive nanocomposite structures that immobilize proteins can synergize the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…For graphite, concerning the individual behavior, both experimental and theoretical work are in line with our results. In ref , simulation revealed that avidin and graphene can form stable complexes primarily via hydrophobic forces and suggested conformational rearrangement near the surface. However, this work uses only one monomer of avidin, while we have utilized the biologically more relevant tetrameric form.…”
Section: Resultsmentioning
confidence: 99%
“…For graphite, concerning the individual behavior, both experimental and theoretical work are in line with our results. In ref , simulation revealed that avidin and graphene can form stable complexes primarily via hydrophobic forces and suggested conformational rearrangement near the surface. However, this work uses only one monomer of avidin, while we have utilized the biologically more relevant tetrameric form.…”
Section: Resultsmentioning
confidence: 99%
“…Because both electrodes were exposed to the same concentrations of biotin, the ΔR ct signal can be assumed to be limited primarily by the amount of avidin initially attached to the surface of the electrode. 48 In particular, the smoother surface of the SP compared to the AJP electrodes allows for a more densely packed avidin layer on the SP electrodes. Moreover, the rougher surface of the AJP electrodes leads to an inhomogeneous distribution of electrochemical properties (e.g., electrochemical current density, interfacial capacitance, and solution resistance) across the surface of the electrode, which induces further deviations from an ideal electrochemical response.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For AV and SA, three polypeptide loops (L3-4, L5-6, and L7-8) cover their binding pockets, among which L3-4 (connect strands β3 to β4) is regarded to play a critical role in ligand binding. This critical loop contains nine residues in AV but only six residues in SA. Therefore, L3-4 of AV is larger and more flexible than that of SA. The lidlike loop L3-4 of AV may adopt an openable conformation, whereas L3-4 of SA has a closed conformation upon ligand binding. , …”
Section: Resultsmentioning
confidence: 99%